2022
DOI: 10.1155/2022/1872412
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Diagnostic Model for Lymph Node Metastasis of the Papillary Thyroid Carcinoma Using Preoperative Ultrasound Features and Imaging Omics

Abstract: In this paper, we mainly adopted 337 patients who had undergone the surgery on lymph node metastasis of papillary thyroid carcinoma (PTC) as the sample population. In order to provide clinical reference for the intelligent decision-making in treatment plan and improvement of prognosis, we utilized ultrasound features and imaging features to construct five early diagnosis models for patients based on the ultrasound features, imaging features, and combined features. The model integrated with broad learning syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Our study also found similar trends, with multifocality and ETE being related to lateral LN metastasis, although central LN metastasis could not be evaluated due to the study’s design comparing N1b with N0. Many studies have shown that multifocality is a risk factor for LN metastasis in PTC and patients with PTMC ( 7 , 31 , 32 ), and there are still controversies regarding its relationship with prognosis. A recent study suggested that minimal ETE is linked to lateral LN metastasis ( 33 ), but there is no association between minimal ETE and recurrence among patients with PTMC ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found similar trends, with multifocality and ETE being related to lateral LN metastasis, although central LN metastasis could not be evaluated due to the study’s design comparing N1b with N0. Many studies have shown that multifocality is a risk factor for LN metastasis in PTC and patients with PTMC ( 7 , 31 , 32 ), and there are still controversies regarding its relationship with prognosis. A recent study suggested that minimal ETE is linked to lateral LN metastasis ( 33 ), but there is no association between minimal ETE and recurrence among patients with PTMC ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the vast majority of research diagnostic models [11,12] focused on predicting the risk of benign and malignant thyroid nodules, cervical lymph node metastasis and postoperative recurrence. However, there are few preoperative evaluations of the clinical high risk of PTMC.…”
Section: Discussionmentioning
confidence: 99%